A method of implementing formalized multidisciplinary collaboration in product conceptual design process. (September 2017) - Yan, Xi-qiang; Li, Yan; Chen, Jian; Li, Wen-qiang; Xiong, Yan
Modern product design can be considered as a process, which involves intensive iteration, complex reasoning, and mutual cooperation among the design groups in different disciplinary areas. In order to meet the requirements of modern products on multidisciplinary collaboration, the traditional method, where the product conceptual design is usually solved only within a single discipline, should be improved. Based on the classic function–behavior–structure model of product conceptual design, this paper studied the collaborative mechanism of functions, behaviors and structures, and proposed a new method/system of implementing formalized multidisciplinary collaboration in the product conceptual design process. In this method, the model/system of conceptual design process with multidisciplinary collaboration was established first, and three collaboration mechanisms were developed. After the coupling relationship among the design sub-states and the disciplinary classification characteristics of the design sub-states were expressed by the mathematical ways, the particle swarm algorithm was applied for the discipline planning, next the solving process for multidisciplinary collaboration were proposed. Finally, the conceptual design process of a stylus printer was used to illustrate the application of the proposed method.